PREVALENCE OF DIFFERENT TYPES OF PEPTIC ULCER DISEASE AND TREATMENT MODALITIES USED BY PATIENTS IN HYDERABAD, SINDH - Rashid, Muhammad Noman; Soomro, Ali Muhammad; Channa, Naseem Aslam; Laghari, Zulfiqar Ali (Pakistan Journal of Physiology, 2016)
Background: Peptic ulcer is mucosal lesion of the stomach or duodenum in which acid and pepsin play major pathogenic role. The major forms of peptic ulcer are gastric ulcer and duodenal ulcer, often caused by Helicobacter pylori, non-steroidal anti-inflammatory drugs (NSAIDs), physiological stress and smoking. The objective of this was to assess the prevalence of different types of peptic ulcer and treatment modalities in peptic ulcer patients. Methods: A total of 425 patients of different age groups were selected from different areas of Hyderabad city having peptic ulcer. There were 166 (39%) male and 259 (61%) females. Data were collected on a questionnaire. Subjects were divided into 5 age groups. Results: Peptic ulcer was more prevalent in age group 20–30 years and mostly found in females (60%) compared to males (40%). Gastric ulcer was seen mostly (68%) compared to duodenal ulcer (32%). The tendency of treatment type came out to be allopathic 38%, homeopathic 4%, and herbal 4%. The tendency of combination therapy was allopathic+homeopathic 34%, homeopathic+herbal 4%, allopathic+herbal 12%, and allopathic+homeopathic+herbal 4%. Conclusion: Gastric ulcer is more common than duodenal ulcer in Hyderabad that is in contrast to reported data. The patients suffering from either types of ulcer preferred allopathic treatment followed by homoeopathy and herbal medication. Pak J Physiol 2016;12(1):6–9